2006
DOI: 10.1002/chin.200635029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Optically Active 2‐Hydroxy Monoesters via‐Kinetic Resolution and Asymmetric Cyclization Catalyzed by Heterometallic Chiral (Salen) Co Complex.

Abstract: Enantioselective syntheses O 0031 Synthesis of Optically Active 2-Hydroxy Monoesters via-Kinetic Resolution and Asymmetric Cyclization Catalyzed by Heterometallic Chiral (Salen) Co Complex.-The utility of the dinuclear heterometallic chiral salen Co-complexes is demonstrated for the asymmetric ring opening of epoxides with carboxylic acids or the asymmetric cyclization of 1-chloro-2-hydroxypropanol derivatives via kinetic resolution. -(LI, W.; THAKUR, S. S.; CHEN, S.-W.; SHIN, C.-K.; KAWTHEKAR, R. B.; KIM*, G.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Kim's group also made efforts to apply Co-salen catalysts in the KR of terminal epoxides with carboxylic acids as nucleophiles. Dimeric Co-salen complexes bridged by the Lewis acids GaCl 3 and Al(NO 3 ) 3 (complex 55 in Scheme 34 and complex 132 in Figure 52) were investigated in the KR of terminal epoxides with a number of different carboxylic acids in TBME [128,169]. The reactions afforded 2-hydroxy monoesters in good yields (35-43%) and with moderate to good enantioselectivities (53-86% ee), but most of the products needed further recrystallization or other treatment to provide practically applicable enantioenriched compounds.…”
Section: With Alcohols Phenols and Carboxylic Acidsmentioning
confidence: 99%
“…Kim's group also made efforts to apply Co-salen catalysts in the KR of terminal epoxides with carboxylic acids as nucleophiles. Dimeric Co-salen complexes bridged by the Lewis acids GaCl 3 and Al(NO 3 ) 3 (complex 55 in Scheme 34 and complex 132 in Figure 52) were investigated in the KR of terminal epoxides with a number of different carboxylic acids in TBME [128,169]. The reactions afforded 2-hydroxy monoesters in good yields (35-43%) and with moderate to good enantioselectivities (53-86% ee), but most of the products needed further recrystallization or other treatment to provide practically applicable enantioenriched compounds.…”
Section: With Alcohols Phenols and Carboxylic Acidsmentioning
confidence: 99%
“…As part of our ongoing research on this issue, we recently reported the utility of bimetallic Schiff base 1 complexes ( Figure 1 ), whose catalytic properties differ from those of well-established monometallic salen 2 complexes [ 6 , 7 , 8 ]. By utilizing dinucleating Schiff bases, we developed heterobimetallic Cu/Sm [ 9 ], Pd/La [ 10 , 11 ], and Ga/Yb [ 12 ] Schiff base complexes, including rare earth metals and homobimetallic Ni 2 [ 13 , 14 , 15 , 16 , 17 , 18 ], Co 2 [ 19 ], and Mn 2 [ 20 ] Schiff base 1 complexes and applied them to various enantioselective reactions (for selected examples of related bifunctional bimetallic Schiff base catalysts, see ref [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]). In this manuscript, we report the details of our efforts to expand the utility of bimetallic Schiff base catalysis for catalytic asymmetric 1,4-addition of β-keto esters to nitroalkenes [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%